2008
DOI: 10.1007/s00134-008-1255-9
|View full text |Cite
|
Sign up to set email alerts
|

Frequent and rare complications of resuscitation attempts

Abstract: We differentiate between frequent and rare complications. The risk of iatrogenic CPR-related trauma is even present with adequate execution of CPR measures and should not question the employment of proven medical techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
130
0
10

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 186 publications
(145 citation statements)
references
References 35 publications
5
130
0
10
Order By: Relevance
“…Estimates of the incidence of some type of resuscitation injury ranges from 21%-65%, 1 and up to 97.4%. 2 Although these injuries infrequently have a significant effect on the patient's outcome, 3 clinicians should be mindful that anterior-posterior chest radiographs underestimate true fracture frequency. 2 Hashimoto et al 1 reported that CPR results in an average of 7.1 broken ribs, with ribs 3-5 being the most frequently involved.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Estimates of the incidence of some type of resuscitation injury ranges from 21%-65%, 1 and up to 97.4%. 2 Although these injuries infrequently have a significant effect on the patient's outcome, 3 clinicians should be mindful that anterior-posterior chest radiographs underestimate true fracture frequency. 2 Hashimoto et al 1 reported that CPR results in an average of 7.1 broken ribs, with ribs 3-5 being the most frequently involved.…”
Section: Discussionmentioning
confidence: 99%
“…Rib injuries occur with greater frequency in women and with increased age. 3 Other CPR-associated injuries that occur with notable frequency (>20% of autopsy cases) include chest abrasion/contusion, defibrillator burns, sternal fractures, upper airway injuries, and pulmonary edema. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Myocardial ischemia caused by acute coronary occlusion can lead to the development of ventricular fibrillation. PCI was thought to be useful in patients with acute ST elevation myocardial infarction (STEMI), [20,21] and it was also beneficial to patients after recovery of spontaneous circulation. [22] Sunde et al [23,24] found that the mortality of patients treated with PCI (n=12) was signifi cantly lower than that of patients treated conservatively (n=20) (17% vs. 70%).…”
Section: Percutaneous Coronary Intervention (Pci)mentioning
confidence: 99%